Micronutrient deficiencies and anaemia associated with body mass index in Australian adults: a cross-sectional study - Evan Atlantis; Canaan Negash Seifu; Paul Patrick Fahey (BMJ Open)
Aim To estimate the prevalence of micronutrient deficiencies and anaemia, and their association with body mass index (BMI) categories among Australian adults.Method We analysed data from the 2011–2013 Australian Health Survey from 3539 participants aged 18 years and over (without known pregnancy) with measured weight and height, and nutrient biomarkers. To address complex sampling, survey weights were used when estimating the prevalence of micronutrient deficiencies (vitamin B12 deficiency; serum vitamin B12<145 pmol/L; iron deficiency; ferritin<30 µg/L and vitamin D deficiency; 25-hydroxyvitamin D<50 nmol/L) and anaemia (haemoglobin <120 g/L for females and <130 g/L for males) and when assessing associations with logistic regression models with adjusted ORs (AORs) for BMI categories: healthy weight (BMI 18.5 to <25.0 kg/m2), reference; overweight (BMI 25.0 to <30.0 kg/m2), obesity class I (BMI 30.0 to <35.0 kg/m2), obesity class II/III (BMI 35.0 kg/m2 or more).Result The prevalence of vitamin B12 deficiency (range 0.9%─2.8%) and anaemia (range 3.9%─6.7%) were variable across BMI groups. The prevalence of iron deficiency in the obesity class I group was 12.0 percentage points lower than healthy weight group with an AOR of 0.50 (95% CI 0.30 to 0.83). The prevalence of vitamin D deficiency in the obesity class II/III group was 7.9 percentage points higher than the healthy weight group with an AOR of 1.62 (95% CI 1.01 to 2.60). Vitamin B12 deficiency and anaemia were not consistently associated with BMI groups.Conclusion We found a consistent association between severe obesity and vitamin D deficiency in Australian adults. We also found obesity class I was negatively associated with iron deficiency, whereas there was no consistent association between BMI groups and vitamin B12 deficiency and anaemia. Public health strategies are needed to prevent vitamin D deficiency in this high-risk population.